Teenage mothers in a pandemic the experiences of early pregnancy in M'lang, North Cotabato - Salazar, Loreen Ysabel G. (2022)
This study discusses the lived experiences and narratives of pregnant and mothering teenagers in the middle of a pandemic. Using the framework of feminist phenomenology, the researcher looked at how young woman make sense of their experiences from their livelihood, early child-bearing and up to their child-rearing. Through the narratives of pregnant and mothering teenagers, the global pandemic is presented as a compounding factor of teenage pregnancy added with several mediating factors such as socioeconomic circumstances, dysfunctional families, pressure from male partners, and lack of access to sexual and reproductive health education. While it can be said that there is extensive literature on teenage pregnancy, primarily focusing on its negative impacts that affect the lives of teenagers, their families, and society as a whole, this study found that teenage pregnancy at this age may not be as bad as how it is represented in existing literature, instead, it is actually already normalized in the community. Hence, it provided a better and wider understanding of their unspoken struggles, while considering different life backgrounds. This study focused on young women?s experiences, thus, further studies should be conducted that include the narratives and perceptions of their male partners to capture a wider perspective of their realities